Seasonal Variation, Antibiotic Resistance of Some Sewage Bacteria from Hamdan Waste Water Treatment Plant in Basrah City-Iraq - Maytham A. Al-Hamdani (Journal of Global Pharma Technology, 2020)
Seasonal variation and antibiotic resistance pattern of some sewage bacteria have been studied during the period of at Hamdan wastewater treatment plant in basrah city-Iraq. The results obtained revealed that there is a seasonal variation in the number of bacteria studied. The bacterial taxa in the present study found to resist several antibiotics. The isolated bacteria are multidrug resistant bacteria. Higher percentage of antibiotic resistance was recorded for bacteria from raw sewage that decreased during the subsequent treatments. Sewage bacteria showed different antibiotic resistance patterns. The effluents to Shatt al-Basrah still contain multidrug resistant bacteria that cause a big health problem through dissemination of multidrug resistant bacteria to the area around.